(untitled) - Steele, Lowell W. (New York, 1989)
IT engineering from mid to large companies, from innovation to intergration
Keywords: Technological innovations,Đổi mới công nghệ,Research, Industrial,Nghiên cứu, công nghiệp; Management,Quản trị,Management,Quản trị